Pengaruh Pemanfaatan Abu Kulit Kerang Sebagai Filler Terhadap Stabilitas Campuran AC-WC - Febri Paramitha Ramadhani; Alfian Malik; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In the highway pavement, fillers have the smallest parts if be compared to coarse and fine aggregates. Fillers that commonly used are Portland cement, limestone, stone ash and fly ash which is relatively expensive. Therefore, there is a need for research by using other alternative materials such as shellfish ash (AKK) which is one of the waste materials that have similar characteristics to cement. The purpose of this study was to test the performance of clamshell ash fillers in AC-WC mixtures that eligible Marshall requirements based on Bina Marga Specification 2010 Revision 3 method using shellfish ash used as fillers in ACWC mixtures. The type of bitumen used in this study is asphalt with penetration of 60/70. In this study, the filler proportion used were 0%, 2%, 4%, and 6% of the total weight of the aggregate mixture. Tests were carried out by using the Marshall test with a variety of treatment periods of 1 day, 4 days, 7 days and 28 days of immersion at 600C temperature. The results showed that Marshall durability with variations in the addition of shellfish ash by 2% with optimum bitumen content 6.3%, has the lowest durability value of 12,95%. While the variation of the addition of shellfish ash by 2% with optimum bitumen content 6.3%, has the highest durability value of 25,28%. This mixture is more resistant to the effects of water on the immersion process. Keywords: Shell ash, AC-WC, Bina Marga Specification 2010 Revision 3, durability